2009
DOI: 10.1017/s1751731109004273
|View full text |Cite
|
Sign up to set email alerts
|

Binational evaluation of type traits from Germany and France with a single-trait MACE animal model

Abstract: Binational genetic evaluation between Germany and France were performed for each type trait using a single-trait MACE (multiple across-country evaluation) model. Daughter yield deviations (DYD) of bulls having 30 equivalent daughter contributions or more were the data for parameter estimation. Full pedigree information of bulls was used via sire and dam relationships. In general, across-country genetic correlation estimates were in agreement with what is observed by Interbull. The estimated correlations were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In this study, except for muscularity traits, the composite traits were consistent with those of dual-purpose Rendena cattle [ 14 ], dual-purpose autochthonous Valdostana cattle [ 30 ], German and French dairy cattle [ 31 ], and Czech Fleckvieh cattle [ 32 ]. Previous studies [ 32 , 33 ] reported muscularity to be a medium to high heritability trait; this differs from the conclusion based on the results of our study and may be due to different definitions of muscularity.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, except for muscularity traits, the composite traits were consistent with those of dual-purpose Rendena cattle [ 14 ], dual-purpose autochthonous Valdostana cattle [ 30 ], German and French dairy cattle [ 31 ], and Czech Fleckvieh cattle [ 32 ]. Previous studies [ 32 , 33 ] reported muscularity to be a medium to high heritability trait; this differs from the conclusion based on the results of our study and may be due to different definitions of muscularity.…”
Section: Discussionsupporting
confidence: 68%